Pengalaman Calon Guru di Era Kurikulum Merdeka - Intan Cezya Sijabat; Jhon Eliezer Naibaho; Wina Ekayanti Sinaga; Septian Immanuel Sinaga; Ruth Melina Sitohang; Kristin Anggreini Siahaan; Immanuel Doclas Belmondo Silitonga (Yayasan Bayt Shufiya Nusantara, 2026)
This study aims to provide an in-depth understanding of the experiences of students from the Program at HKBP Nommensen University Pematangsiantar during their Field Teaching Practice (PPL) at Taman Madya (Private) Tamansiswa Senior High School in the 2025 academic year. Over fourteen weeks (August 20–December 10, 2025), the students engaged in teaching activities, lesson plan development, and non-instructional programs within the framework of the Merdeka Curriculum (Independent Curriculum). Employing a narrative study approach, this research positions student experiences as the primary data source to explore reflective learning processes and the formation of professional teacher identity. The findings reveal that PPL serves as a dialectical space where pedagogical theories learned at the university intersect with the dynamic social realities of the school environment. Three key findings emerged: first, the consistency between theory and practice is expressed through the students’ reflective capacity to interpret and adapt theoretical knowledge to contextual realities; second, the mentoring relationship between student teachers and supervising teachers demonstrates a shift from hierarchical supervision toward collaborative partnership that fosters mutual learning; and third, student teachers’ responses to contemporary educational issues—particularly digitalization and the Merdeka Curriculum—encourage the development of technology-based learning innovations and critical literacy practices. The study concludes that PPL not only equips student teachers with instructional competencies but also cultivates professional awareness, pedagogical autonomy, and social sensitivity—qualities that form the foundation of effective and human-centered teachers in an era of educational transformation.